Exosomes transfer miRNAs from cell-to-cell to inhibit autophagy during infection with Crohn’s disease-associated adherent-invasive E. coli - Anaïs Larabi; Guillaume Dalmasso; Julien Delmas; Nicolas Barnich; Hang Thi Thu Nguyen (Gut Microbes, 2020)
Adherent-invasive E. coli (AIEC), which abnormally colonize the intestinal mucosa of Crohn’s disease (CD) patients, are able to adhere to and invade intestinal epithelial cells (IECs), survive and replicate within macrophages and induce a pro-inflammatory response. AIEC infection of IECs induces secretion of exosomes that increase AIEC replication in exosome-receiving IECs and macrophages. Here, we investigated the mechanism underlying the increased AIEC replication in cells receiving exosomes from AIEC-infected cells. Exosomes released by uninfected human intestinal epithelial T84 cells (Exo-uninfected) or by T84 cells infected with the clinical AIEC LF82 strain (Exo-LF82), the nonpathogenic E. coli K12 strain (Exo-K12) or the commensal E. coli HS strain (Exo-HS) were purified and used to stimulate T84 cells. Stimulation of T84 cells with Exo-LF82 inhibited autophagy compared with Exo-uninfected, Exo-K12 and Exo-HS. qRT-PCR analysis revealed increased levels of miR-30c and miR-130a in Exo-LF82 compared to Exo-uninfected, Exo-K12 and Exo-HS. These miRNAs were transferred via exosomes to recipient cells, in which they targeted and inhibited ATG5 and ATG16L1 expression and thereby autophagy response, thus favoring AIEC intracellular replication. Inhibition of these miRNAs in exosome-donor cells infected with AIEC LF82 abolished the increase in miR-30c and miR-130a levels in the released Exo-LF82 and in Exo-LF82-receiving cells, thus suppressing the inhibitory effect of Exo-LF82 on ATG5 and ATG16L1 expression and on autophagy-mediated AIEC clearance in Exo-LF82-receiving cells. Our study shows that upon AIEC infection, IECs secrete exosomes that can transfer specific miRNAs to recipient IECs, inhibiting autophagy-mediated clearance of intracellular AIEC.